Controlled growth and characterization of In2O3 nanowires by chemical vapor deposition. (March 2019) - Feng, Cuiying; Liu, Xiaocan; Wen, Shuai; An, Yukai
Abstract: The high-crystalline indium oxide (In2 O3 ) nanowires were deposited by chemical vapor deposition (CVD) method on Si (111) substrates using C and In2 O3 powders as the raw materials. The morphology, microstructures and the valences analysis of In2 O3 nanowires were characterized by XRD, SEM, EDS, XPS and TEM techniques. The length and density of In2 O3 nanowires can be effectively controlled by adjusting the experimental parameters. The optimal growth condition is obtained, namely the Au catalyst thickness of 12 nm, growth temperature of 1050 °C and Ar flow rate of 200 sccm. The cubic bixbyite structure as pure In2 O3 (space group I a 3 ¯ ) as well as large amounts of oxygen vacancies can be observed in the deposited In2 O3 nanowires. The photoluminescence (PL) spectrum shows an ultraviolet emission peak located at 390.6 nm and two luminescence peaks located at 423.6 nm and 436.5 nm, which can be attributed to the near-band-edge emission and the presence of oxygen vacancy defects in the In2 O3 nanowires, respectively. Highlights: The high-crystalline indium oxide nanowires were deposited by CVD method. The length and density of In2 O3 nanowires can be effectively controlled. An ultraviolet emission peak and two violet luminescence peaks were observed. PL spectrum originates from the near-band-edge emission and oxygen vacancies.